Reversible EMT and MET mediate amnion remodeling during pregnancy and labor - Richardson, Lauren S; Taylor, Robert N; Menon, Ramkumar (Science signaling, 2020)
The amnion is remodeled during pregnancy to protect the growing fetus it contains, and it is particularly dynamic just before and during labor. By combining ultrastructural, immunohistochemical, and Western blotting analyses, we found that human and mouse amnion membranes during labor were subject to epithelial-to-mesenchymal transition (EMT), mediated, in part, by the p38 mitogen-activated protein kinase (MAPK) pathway responding to oxidative stress. Primary human amnion epithelial cell cultures established from amnion membranes from nonlaboring, cesarean section deliveries exhibited EMT after exposure to oxidative stress, and the pregnancy maintenance hormone progesterone (P4) reversed this process. Oxidative stress or transforming growth factor-β (TGF-β) stimulated EMT in a manner that depended on TGF-β-activated kinase 1 binding protein 1 (TAB1) and p38 MAPK. P4 stimulated the reverse transition, MET, in primary human amnion mesenchymal cells (AMCs) through progesterone receptor membrane component 2 (PGRMC2) and c-MYC. Our results indicate that amnion membrane cells dynamically transition between epithelial and mesenchymal states to maintain amnion integrity and repair membrane damage, as well as in response to inflammation and mechanical damage to protect the fetus until parturition. An irreversible EMT and the accumulation of AMCs characterize the amnion membranes at parturition.